Bagaimanakah Pengendalian Kecelakaan Kerja pada Pemasangan Pipa Pemadam Kebakaran di PT “PTC”? - Pipit Marfiana (Gema Wiralodra, 2022)
Every year there are more than 250 million accidents in the workplace and more than 160 million workers get sick. In addition, 1.2 million workers died due to accidents. Occupational Health and Safety which has been popularly known as K3, and is widely spread in every industrial sector. Therefore, this study aims to describe the program, procedure, implementation, and control of work accidents in the installation of fire extinguishers at PT "PTC". This research is a qualitative research with a descriptive case study design. The data collection techniques used were interviews, field observations, and literature studies. The data that has been collected is then analyzed qualitatively. The results of the study concluded that PT “PTC” had implemented a work accident control program, namely by conducting health checks on workers, safe work permits, personal protective equipment, and safety driving. The hazard control procedure has implemented the Internal Work Procedure NO. C-401/F13435/2015-S0 related to “Hazard Identification and Risk Assessment” as a work accident control procedure, at PT “PTC”. In addition, it has implemented the implementation of work accident control in accordance with Law no. 1 of 1970 concerning occupational safety as an aspect of the occupational safety and health management system to support existing work programs. This is an effort to continue to develop K3 procedures that are integrated with work processes to increase work productivity and participate in the implementation of occupational safety and health (K3) aspects.